The Rise of Brand Love and E-Vocacy in Electric Vehicle Marketing – A Systematic Review - Leo, Gundur; Sutrisno, Rivan; Sakova, Megha (Integrasi Sains Media, 2025)
As the electric vehicle (EV) sector shifts from a niche to a mass market, traditional cognitive-based marketing models are inadequate for explaining deep consumer loyalty. This Systematic Literature Review (SLR) synthesizes the evolution of green marketing stimuli and their impact on consumer advocacy. Adhering to PRISMA guidelines, we analysed 33 high-impact empirical studies (2020–2025) to construct an enhanced Stimulus-Organism-Response (S-O-R) framework integrated with Signalling Theory. The results reveal three critical paradigm shifts. First, generic